Development of Mathematics Learning Media "MedLearn Math" on Three Variable Linear Equation Systems Material - Hidayati, Herlina; Rakhmawati, Astri; Zulkifli, Zulkifli (Jurnal Ilmiah Mandala Education (JIME), 2024)
This research was motivated by the basic problems of students, namely difficulties in understanding the material on Systems of Linear Equations with Three Variables, how to use methods to solve them, and not maximizing the use of technology as a learning medium. The aim of this research is to develop learning media in the form of a MedLearn Math on three-variable linear equation systems. This development research uses the ADDIE model. The results of the research show that the level of feasibility of media and material experts received a very feasible category with scores of 97% and 90% respectively. The results of students' responses to the media obtained an average percentage of 83.3% in the very good category, while the test results of 3 randomly selected students obtained an average percentage of 89.2% in the very good category. So, the MedLearn Math developed as a learning medium on three-variable linear equation systems is "very feasible" and "very good" and easy to use anytime and anywhere.